The Challenges Faced by Medical Personnel Misusing Drugs: A Phenomenological Study - Anita Fafa Dartey; Vivian Tackie; Ben Okon Inemesit; Beatrice Bella Johnson; Comfort Worna Lotse; Silvia Geraldo; Millicent Afeafa Afedzo; Alfred Ofori Agyemang (SAGE Open)
Certain medicinal products, like pain medications and stress-reducing drugs, with therapeutic benefits but psychoactive side effects, may be misused, especially among medical personnel. This study used a phenomenological study design. A semi-structured interview guide was used to collect data from respondents. The data gathered were transcribed verbatim, reviewed thoroughly by the researchers, and analyzed. The study presents evidence on healthcare workers’ drug misuse, including withdrawal challenges, life impacts, and coping strategies. It emphasizes professional help, diversional therapy, boundaries, and support. It highlights the challenges of seeking assistance and calls for comprehensive efforts, recommending policies in healthcare organizations to address this issue. Based on the study’s findings, a specialized training program to detect substance misuse, a dedicated hotline for reporting difficulties, as well as providing assistance and services for healthcare staff struggling with drug misuse are all recommended.